A revision of the western North Pacific swellsharks, genus Cephaloscyllium Gill 1862 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae), including descriptions of two new species - Schaaf-Da Silva, Jayna A.; Ebert, David A. (Zootaxa, 2008)
The genus Cephaloscyllium Gill 1862 (Chondrichthyes, Carcharhiniformes, Scyliorhinidae) until recently had only two species recognized, C. isabellum [= C. umbratile (Jordan & Fowler 1903)] and C. fasciatum Chan 1966, from the western North Pacific (WNP), with one dubious species, C. formosanum, having been described by Teng in 1962. Recently, three additional species were described, C. circulopullum Yano et al. 2005, C. sarawakensis Yano et al. 2005, and C. parvum Inoue & Nakaya 2006 from this region. Here we present a revision of this genus for the WNP, including redescriptions of C. fasciatum and C. umbratile based on the holotypes, a re-examination of the recently described species, and descriptions of two new species from Taiwan. Cephaloscyllium umbratile can be distinguished from its congeners based on maximum size, length of first dorsal-fin base, anal–caudal space, and dorsal–caudal space. We conclude, based on a comparison of C. parvum and C. sarawakensis, that the former is a junior synonym of the latter species. The two new Taiwanese species can be separated from other WNP species by color pattern, shape of the anterior nasal flap, anal and dorsal-fin size, internarial width, and mouth size. Finally, we present a revised dichotomous key to the WNP Cephaloscyllium recognizing six contemporary taxa: C. circulopullum, C. fasciatum, C. sarawakensis, C. umbratile, C. pardelotum sp. nov. and C. maculatum sp. nov.